2017
DOI: 10.11648/j.ogce.20170505.13
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Feasibility of Simulating the Distillation Curves and ASTM Distillation Temperature

Abstract: Abstract:For the reliable design of crude oil and residua fractionators and fired heaters, accurate calculation method for ASTM Distillation curves and ASTM distillation temperature at the required volume percentage distilled is necessary. The present work deals with fitting literature data of ASTM Distillation curves and obtain a new correlation suitable to use in modeling when optimizing the refining processes, such as distillation, FCC, catalytic reforming, hydrotreating, etc. The results showed that the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…The papers [8,9] are focused on comparing the literature data with ASTM distillation curves and obtaining a new correlation suitable for use in modeling to optimize refining procedures, such as distillation, catalytic reforming, and hydro treatment. The results showed that the values predicted by the new correlation correspond to the literature report.…”
Section: Methodsmentioning
confidence: 99%
“…The papers [8,9] are focused on comparing the literature data with ASTM distillation curves and obtaining a new correlation suitable for use in modeling to optimize refining procedures, such as distillation, catalytic reforming, and hydro treatment. The results showed that the values predicted by the new correlation correspond to the literature report.…”
Section: Methodsmentioning
confidence: 99%